The Clifford Algebra of the Density Matrix: An Elementary Approach - (:unkn) unknown (Springer Nature Switzerland, 2024)
This work studies the Clifford algebra approach to the density matrix. We discuss elementary examples of pure and mixed states by writing the density matrix as an element of the Clifford algebra of the three-dimensional space . We also revisit the pheno...
Keywords: Álgebra de Clifford; Matriz de densidad